2009
DOI: 10.1002/ajmg.a.32853
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, longitudinal study of the impact of GJB2/GJB6 genetic testing on the beliefs and attitudes of parents of deaf and hard‐of‐hearing infants

Abstract: There are limited data on the impact of incorporating genetic counseling and testing into the newborn hearing screening process. We report on results from a prospective, longitudinal study to determine the impact of genetic counseling and GJB2/GJB6 genetic testing on parental knowledge, attitudes, and beliefs about genetic testing. One hundred thirty culturally hearing parents of 93 deaf or hard-of-hearing children ages 0 -3 years primarily identified through newborn hearing screening received pre-and post-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 48 publications
2
38
0
1
Order By: Relevance
“…[43][44][45] GJB6 deletions have been observed in multiple populations, although they appear to be a relatively uncommon explanation for hearing loss in the United States. [46][47][48] Notably, hearing loss caused by certain dominant mutations in GJB2, although uncommon, may present as a syndromic hearing loss, with associated skin findings. [49][50][51] Nonsyndromic mitochondrial hearing loss is characterized by audiograms that fall into the moderate-to-profound range and is associated with variants in either the MT-RNR1 gene encoding the mitochondrial 12S ribosomal RNA or the MT-TS1 gene encoding the mitochondrial transfer RNA Ser(UCN).…”
Section: Genetic and Nongenetic Etiologies Of Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] GJB6 deletions have been observed in multiple populations, although they appear to be a relatively uncommon explanation for hearing loss in the United States. [46][47][48] Notably, hearing loss caused by certain dominant mutations in GJB2, although uncommon, may present as a syndromic hearing loss, with associated skin findings. [49][50][51] Nonsyndromic mitochondrial hearing loss is characterized by audiograms that fall into the moderate-to-profound range and is associated with variants in either the MT-RNR1 gene encoding the mitochondrial 12S ribosomal RNA or the MT-TS1 gene encoding the mitochondrial transfer RNA Ser(UCN).…”
Section: Genetic and Nongenetic Etiologies Of Hearing Lossmentioning
confidence: 99%
“…Benefits can include providing etiologic information, identifying (or allaying concerns about) comorbidities that may need referral for specialty care, planning for future medical and educational needs, facilitating estimations of the likelihood of recurrence, allowing families to better plan for the birth of a deaf or hard-of-hearing child, relieving the guilt that some parents may feel about having a child with hearing loss, enhancing ACMG PrACtiCe Guidelines psychological well-being, dispelling misinformation, and facilitating referral for unrelated hereditary conditions such as familial cancer. 48,[70][71][72][73][74][75][76][77][78][79] Furthermore, if mitochondrial DNA mutations associated with genetic susceptibility to aminoglycoside ototoxicity are discovered, it may be possible for relatives to avoid precipitating medications. [53][54][55] As with any genetics evaluation, clear communication between the genetics professionals and their patients is important for the provision of effective genetics services.…”
Section: The Importance Of Genetic Evaluation and Genetic Counseling mentioning
confidence: 99%
“…La extrema heterogeneidad genética de la sordera históricamente ha supuesto una dificultad a la hora de integrar el diagnóstico genético en la práctica clínica. Sin embargo, los beneficios de obtener un diagnóstico etiológico son incuestionables, pues nos proporciona información pronóstica y reproductiva, contribuye a reducir la ansiedad en el paciente y sus familiares, nos permite descartar o prever manifestaciones sindrómicas potencialmente graves, evita la realización de pruebas diagnósticas innecesarias y, en ocasiones, resulta útil en la toma de decisiones terapéuticas (Robin et al, 2005) (Cabanillas y Cadiñanos, 2012) (Palmer et al, 2009). …”
Section: Discussionunclassified
“…Several studies have evaluated parental attitudes toward genetic testing for pediatric deafness, including prenatal diagnosis. The data demonstrated the importance of an accurate genetic counseling and indicated the great interest of the parents in prenatal genetic testing (Abe et al 2010;Brunger et al 2000;Kaimal et al 2007;Li et al 2007;Palmer et al 2009;Steinberg et al 2007).…”
Section: Introductionmentioning
confidence: 92%
“…Somer et al (1988) obtained similar results in an earlier study where 80 % of individuals or couples counseled between 1972 and 1981 showed adequate knowledge about the mode of inheritance and 74 % about the chance of recurrence. Other reports indicate that parents can understand concepts of inheritance, genetic origin and the chance of recurrence after genetic counseling (Abe et al 2010;Michie et al 1997;Palmer et al 2009). In contrast, Brunger et al (2000) found that parents had a very poor understanding of the inheritance of deafness, and little understanding of genetic mechanisms and recurrence risk, suggesting they may not have received genetic counseling or that the genetic counseling they received was inadequate.…”
Section: Recall Of Information: the Chance Of Recurrence And The Inhementioning
confidence: 99%